PERKEMBANGAN LINGKUNGAN NEIGHBORHOOD UNIT SEBAGAI PENATAAN FISIK - Hasanuddin, Nurul Lestari (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
The neighborhood unit was originally a rural community in the form of small units in order to form a close and ideal relationship, both in terms of sociology and physical aspects. Is Clerence Perry who later popularized the term neighborhood unit into a strategy to revitalize the urban environment in America. The principles of neighborhood units are closely related to the arrangement and physical infrastructure of the environment such as internal street system, open spaces, institutional site, and local shops. From this initial thought, it encouraged several urban planners to create and develop a plan that prioritized these objectives by adjusting to the issues that were happening. This concept continues to grow and is adapted to the conditions of each environment. In the past decade, various improvements and updates have been made to accommodate new ideas in urban planning and design. As developed by Duany, Zyberk, and Alminana in 2003 which was called the update neighborhood unit and also Douglas Farr in 2008 with its sustainable neighborhood unit. Then the concept of the neighborhood unit expanded to Asia. Planners and developers can vary by adjusting the local context in each country. These changes and developments from the neighborhood unit will be reviewed and compared so that they can strengthen their potential if applied in Indonesia.